Business Networking and Internationalization: Testing the Mediation Role of Organizational Learning - Sendawula, Kasimu; Ngoma, Muhammed; Bananuka, Juma; Kimuli, Saadat Nakyejwe Lubowa; Kabuye, Frank (World Journal of Entrepreneurship, Management and Sustainable Development, 2020)
The purpose of this study was to establish the mediation role of organizational learning in the relationship between business networking and internationalization of manufacturing small and medium-sized enterprises (SMEs) using evidence from Uganda. This study is cross sectional and correlational. Data were collected through a questionnaire survey of 96 manufacturing SMEs. Data were analyzed through correlation coefficients, hierarchical regression and mediation analysis using Statistical Package for the Social Sciences and MedGraph - Excel Version.
Keywords: s Internationalization, Business networking, Organizational learning, Small and medium-sized enterprises, Uganda